Influence of big five personalities on knowledge sharing behaviour among librarian / Raja Alwi Raja Omar, Abd Latif Abdul Rahman and Muhammad Firdaus Helmi - Raja Omar, Raja Alwi; Abdul Rahman, Abd Latif; Helmi, Muhammad Firdaus (Research Management Institute, 2014)
As a resourceful asset of an organization, knowledge needs to be effectively managed and manipulated to become leverage in organizational competitive environment. Knowledge Management concept and system was introduced to ensure sustainable success of an organization. Knowledge sharing is one important process in knowledge flowing and flourish within an organization. However, knowledge sharing process could also be affected by other factors and one of the factors identified is knowledge sharing behavior. Besides that, there is also a strong inclination to believe that personality or personal characters could influence a persons’ behavior towards knowledge sharing. A person’s character or personality is belief to cloud their behavioral response on whether to share or not to share knowledge. This study attempts to investigate the impact of Big Five Personality (BFP) factors on knowledge sharing behavior among librarians in Northern Peninsular Malaysia. Five dimensions of Big Five Personality factors are investigated namely extraversion, agreeableness, conscientiousness, neuroticism, and openness. The study looks at personality influence on knowledge sharing behavior among librarians within the same library and between librarians of other libraries. These are evaluated against the intention to share knowledge provided by libraries, using an online survey method to gauge knowledge sharing behavior among librarians in northern region of Peninsular Malaysia. Quantitative data were analysed using the Statistical Package for Social Sciences (SPSS) and SmartPLS version 2.0. The findings indicated that between the agreeableness, conscientiousness, and openness personality traits or dimensions, agreeableness seems stronger in performing knowledge sharing by librarians at interlibrary level as it altruistic, generous, and pleasant nature suits more compared to an intra-organization environment. The study also found that librarians with high level of extraversion personality trait to have more favourable or positive intention towards knowledge sharing behavior. The findings also show a strong relation between intention and behavior where librarians’ intention to share influence their positive behavior towards knowledge sharing. Further study could be generated in different circumstances such as the forms of knowledge or the personal interest that may encourage or prohibit knowledge sharing among librarians.